Feasibility Analysis of Garlic Farming Business and Income Contribution in Magelang Regency - Aulia Shabila Riany; Imanuddin Muhamad; Nur Fajri Wahid; Widyastuti Winda (E3S Web of Conferences)
Garlic is an agricultural commodity with benefits as a kitchen spice and traditional medicine. Garlic is a horticultural commodity that plays an important role in Indonesia’s maintaining the economy and national food security. Garlic cultivation is rare in Indonesia. Only three garlic centers exist in Central Java, West Nusa Tenggara, and West Sumatra. One of the garlic centers in Central Java is in Magelang Regency. However, garlic production in the Regency has decreased from 2013 to 2017. The government is trying to achieve self-sufficiency of garlic to increase garlic production. This caused researchers to research garlic businesses and their contribution to farmers’ income. The resulting analysis can help the government create policy programs to support increased garlic production and support farmers in continuing to carry out garlic farming sustainably. The study results showed that the average farmer income was IDR 35,411,324 per hectare with an income of IDR 88,232,387 per hectare. The contribution of garlic farming to farmers’ income is 47.63 percent, which is included in the moderate category